Development of assays for therapeutic screening in myotonic dystrophy - Udosen, Inyang Udofia (2012)
Myotonic dystrophy (DM) is an autosomal dominant inherited multisystemic neuromuscular disease. The molecular mechanism for DM is mediated by toxic RNAs containing expanded repeat units. DMI is caused by a CTG repeat expansion in 3'-UTR of the DMPK gene while DM2 is caused by CCTG repeat in intronl of the ZNF9 gene. The molecular features of DM are formation of RNA foci, co-localisation of MBNL proteins with ribonuclear foci, splicing defects of a subset of pre-mRNAs with elevation ofCUGBPI in DMl. In order to develop therapy for DM, assays were designed based on the molecular characteristics of the disease to screen compounds. Two primary assays were based on disruption of nuclear foci and on correction of misregulated splicing involving intron2 CLCNI. The first part of this report deals with the development of a nuclear foci assay and splicing construct assay. Both assays were optimised in HTS and utilized in screens for molecules that clear nuclear foci from DM cells and correct misregulated splicing in intron2 of CLCNI respectively. High throughput screens of kinase and phosphatase inhibitor libraries using the nuclear foci assay and CLCNI splicing construct assay yielded two positive hits: protein kinase C inhibitors designated in the compound library as D8 (hypericin) and D9 (Ro-31-8220). The second part of this thesis deals with the confirmation of compound hits obtained from the primary screen. I examined two aspects: mutant DMPKtranscript entrapment in nucleus and splicing defects associated with the disease. A BpmJ restriction assay was used to test the effect of compounds on mutant DMPK transcripts showed that both D8 and D9 were unable to release the mutant transcript into the cytoplasm. D8 demonstrated efficacy in reversing spliceopathy in alternative splicing assays of JR, SERCAI MBNLI and MBNL2 while D9 did not have this effect except on MBNLI which showed a very minor efficacy.